Study of the effect of solvent on the conductivity of langmuir-schaefer films of Poly(Fullerene)s - Roncaselli, Lucas K. M. [UNESP] (2021)
The present work aims to prepare and characterize very thin films of poly(fullerene)s in order to investigate their electrical properties and the influence of xylene and chloroform solvents on these materials. The fullerenes studied were phenyl-C61-butyric acid methyl ester (PCBM), oligo{(phenylC61-butyric acid methyl ester)-alt-[1,4-bis(bromomethyl)-2,5-bis(octyloxy)benzene]} (OPCBMMB) and poly{[bispyrrolidino(phenyl-C61-butyric acid methyl ester)]-alt-[2,5-bis(octyloxy) benzene]} (PPCBMB), along with poly(3-hexylthiophene) (P3HT). The Langmuir-Schaeffer technique was used to prepare films, which were deposited on interdigitated gold substrates, and electrically characterized, with emphasis on the study of transport, conductivity and mobility mechanisms with respect to the solvents used. We found that the addition of P3HT significantly increased the conductivity of these materials. The xylene cast PPCBM, in both pure and mixed forms under dark conditions, presented the best conductivity results with respect to the other materials. However, when chloroform was used, it was found that OPCBMMB in both pure and mixed forms under light, exhibited the best conductivities. This is the first treatment, to our knowledge, of the impact of solvents on the electronic properties of poly(fullerene)s.